The Incremental Value of Controlling for Covert Insufficient Effort Responding - Castille, Ann-Marie R.; Castille, Christopher M.; Sharma, Sandesh (Journal of Organizational Psychology, 2021)
Insufficient effort responding (IER) is a common concern of survey researchers especially those who collect data through crowdsourcing. Methods of controlling for IER may be overt (identifiable by respondents) or covert. This study examines the relative impact of controlling for covert IER when overt-IER methods are in the survey design. Using data from an experiment on performance feedback reactions where overt IER controls were in place, we examine the scale reliabilities and convergent and discriminant validity, both of which change negligibly by controlling for covert IER. Findings suggest controlling for covert IER lacks incremental value beyond controlling for overt IER.